2013
DOI: 10.1021/ma4015406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyolefin/Layered Silicate Nanocomposites via Surface-Initiated Ring-Opening Metathesis Polymerization

Abstract: Here we report the synthesis and characterization of block copolymer/layered silicate (BCPLS) nanocomposites via the surface-initiated ring-opening metathesis polymerization (SI-ROMP) of norbornene and cyclopentene from montmorillonite clay (MMT). The MMT particle surfaces were functionalized with a norbornene-terminated alkylammonium surfactant through ion exchange. Block copolymer brushes of norbornene and cyclopentene were polymerized directly from the surface of these functionalized clay platelets, yieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…MBB samples (4c) and (4d) may particularly be interesting in processing perspective in that the addition of MMT does not significantly change the rheological characteristics. This is also observed by our work in synthesizing MBBs via ring‐opening metathesis polymerization (ROMP) mechanism but an entirely different system . Although these results show promise for designing a stronger or tougher MBB, more research is needed before any conclusive statements can be made.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBB samples (4c) and (4d) may particularly be interesting in processing perspective in that the addition of MMT does not significantly change the rheological characteristics. This is also observed by our work in synthesizing MBBs via ring‐opening metathesis polymerization (ROMP) mechanism but an entirely different system . Although these results show promise for designing a stronger or tougher MBB, more research is needed before any conclusive statements can be made.…”
Section: Resultsmentioning
confidence: 99%
“…This is also observed by our work in synthesizing MBBs via ring-opening metathesis polymerization (ROMP) mechanism but an entirely different system. 36 Although these results show promise for designing a stronger or tougher MBB, more research is needed before any conclusive statements can be made.…”
Section: Full Papermentioning
confidence: 97%
“…In 1999, Grubbs et al [37] first reported the surface-initiated ROMP (SI-ROMP) of norbornene derivative from gold surface with Grubbs 1st generation catalyst. Subsequently, many reports displayed the successful SI-ROMP from various surface including silicon wafers [38], silica nanoparticles [39], carbon nanotubes [40], carbon paper [41], cellulose fibers [42], montmorillonite clay [43] and other substrates [44], suggesting that ROMP is an important polymerization strategy for the synthesis of a variety of polycycloolefins, such as polynorbornene (PNb), as non-polar polyolefins that can be introduced onto polar materials to effectively tailor the performance of substrates. Our research group recently reported the successful preparation of the surface-bound PNb films from Si/SiO 2 substrates by SI-ROMP, and described a strategy to prevent the degradation during the epoxidation of grafted PNb chains just by solvent effect under mild conditions [45].…”
Section: Introductionmentioning
confidence: 99%
“…123,126,145 Recently our group has observed that surface-initiated polymerization (SIP) could result in high graft densities to form brush regime and the resultant steric forces could also result in highly exfoliated nanocomposites. 115,116,131 Based on the type of processing technique being used, different degrees of mixing for polymer and clay could be achieved resulting in mainly three types of structures: phase separated, intercalated or exfoliated structures as visualized in figure 5.1. Depending on the type of polymer, layered silicate,polymerization chemistry and degree of dispersion of clay expected, different approaches for SIP could be employed.…”
Section: Introductionmentioning
confidence: 99%
“…118,144,145 A surfactant for clay modification was developed in our previous work which nearly doubled the d-spacing for modified clay compared to pristine one. 131 The monomers used in the current work are similar to those used in our previous work, so we decided to use the same surfactant modifier for the clay. Ring opening metathesis polymerization (ROMP) is usually employed for the polymerization of cyclic olefins.…”
Section: Introductionmentioning
confidence: 99%